CIT Rate and Tax Holiday as Tax Competition Tools to Attract Inward FDI in ASEAN-6 - Pitaloka, Ratri Bening; Slamet, Kuwat (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
This study examines how tax competition, through statutory Corporate Income Tax (CIT) rates and tax holiday schemes, affects inward foreign direct investment (FDI) in the ASEAN-6 countries: Indonesia, Singapore, Malaysia, Thailand, the Philippines, and Vietnam. Using panel data from 2014 to 2023, the analysis employs a feasibility test, complemented by T-tests, F-tests, R² tests, path analysis, and hypothesis testing to assess the direct and indirect effects of tax competition instruments on FDI. The findings reveal that tax competition via the CIT rate significantly influences FDI in partial and simultaneous models. Conversely, tax holidays demonstrate a significant impact only when examined simultaneously, not individually. When both instruments are analyzed, they exert a statistically significant combined effect, with a total impact value of 0.472. These results suggest that while CIT reductions are more effective as standalone tools, the coordinated use of both CIT cuts and tax holidays can enhance the effectiveness of tax competition in attracting FDI. However, the effectiveness of such incentives depends on policy design and institutional readiness. Therefore, policymakers in ASEAN-6 are encouraged to adopt a multidimensional strategy that integrates well-targeted fiscal incentives with broader institutional and structural reforms to foster investor confidence and support a more resilient investment climate.